Identifying Language Disorder Within a Migration Context: Development and Performance of a Pre-school Screening Tool for Children With German as a Second Language - Holzinger, Daniel; Weber, Christoph; Jezek, Magdalena (Frontiers in Pediatrics, 2022)
Background: There is a lack of accurate and practicable instruments for identifying language disorders in multilingual children in pre-school settings. Objective: To develop a language screening instrument for pre-school children who are growing up with German as their second language. Design: After the development and initial validation of a language screening tool, the new instrument (LOGiK-S) was administered to three cohorts of children (2014, 2015, 2017) with a non-German first language attending a variety of public pre-schools in Upper Austria. The screening instrument measures expressive and receptive grammatical skills in German. The final validation study included the results for 288 children for the screening measure and reference tests. A combination of a standardized comprehensive language test of grammatical skills developed for children acquiring German as a second language and a test of expressive vocabulary with the use of specific cutoffs for second language learners was applied as the gold standard for identifying language disorders. Results: The LOGiK-S screening of expressive grammar demonstrated excellent accuracy (AUC .953). The screening subscale of receptive grammar did not improve the prediction of language disorders. Using an optimized cutoff yielded a fail rate of 17%, excellent sensitivity (0.940), and specificity (0.936). Time economy and acceptance of the screening by children and screeners were mostly rated as high. Conclusion: The LOGiK-S language screening instrument assessing expressive German grammar development using bilingual norms is a valid and feasible instrument for the identification of language disorders in second language learners of German at the pre-school age.